RANCANG BANGUN WEB SERVER UNTUK MESIN PENGERING RUMPUT LAUT BERBASIS INTERNET OF THINGS - Dwi Cahyono , Tomy; Sasmita Susanto , Eri; Darmawan, Indra (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
This study aims to design and build a web server for a machineinternet of things (IoT) based seaweed dryer works to dry the grassfrom wet to dry wire with thermonitory heat. Hot temperatureis the main factor determining the drying duration. This researchusing the waterfall software development method and built withusing PHP 7 and javascript. Methods of data collection using techniquesobservation, interview and literature study and using black box testing methodthat is, testing is done by testing the software in terms of functionality.The result of the research is that the web can be accessed through a website equipped withuser management features so that they can contribute to Samawa employeesinspiration.